TAX TECHNOLOGIES OF RESULTS OF CALCULATIONS FOR PAYMENTS TO EMPLOYEES - Kostyshyn, Nataliia (SWorld-Ger Conference proceedings, 2024)
The work demonstrates the peculiarities of tax technologies in relation to the compliance and legality of the company’s calculations of employee benefits. Deficiencies are identified and ways to eliminate them are proposed. In our opinion, an effective wa